Total teater. Samhällsutopier på scen under Weimarrepubliken - Jonsson, Stefan (K&K - Kultur og Klasse, 2012)
TOTAL TEATER - STAGING UTOPIA IN THE WEIMAR REPUBLIC  | Highlighting a crucial topic in the utopian aesthetics developed in the European interwar period, this article discusses the radical ideas of placing society on stage, and of turning theatre into a medium for the self-representation of society. Illustrations and examples are drawn mainly from Erwin Piscator, and his collaboration with Walter Gropius in a project that they conceived of as “the Total Theatre” (Das Totaltheater). As the essay argues, these ideas of a new stage craft and performance were perhaps the most daring interventions among the wild and unruly democratic experiments of the Weimar Republic, and they usefully illustrate what Walter Benjamin had in mind as he, in the same period, cryptically endorsed the aesthetico-political idea of an artwork that is “being absorbed by the masses”.